COVID-19: Lockdowns, Fatality Rates and GDP Growth. Evidence for the First Three Quarters of 2020 - Michael König; Adalbert Winkler (Intereconomics, 2021)
The COVID-19 pandemic has triggered an unprecedented economic crisis. This article analyses the impact of mandatory social distancing imposed by lockdown policies and voluntary social distancing triggered by COVID-19 fatality rates on GDP growth in the first three quarters of 2020 for a sample of 42 countries. OLS and IV results indicate an important role for the fatality rate, while panel regressions show that lockdown stringency is the more important driver of growth. When including lagged variables, more restrictive measures lead to lower GDP growth in the same quarter but are associated with a positive, catching-up effect in the following quarter.
Keywords: 330; Coronavirus; Sterblichkeit; Gesundheitspolitik; Konjunktur; Regressionsanalyse